ОСОБЕННОСТЬ СВОЙСТВА НОВИЗНЫ СЕМАНТИЧЕСКИХ ОККАЗИОНАЛИЗМОВ - Молодчая, Наталья Сергеевна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The article deals with the property of novelty inherent to аІІ the types of nonce words. Factors detennining the specifics of semantic nonce words' property of novelty are analyzed. Asymmetry, Gestalt-image, subjective associations are argued to create unpredictability, expressed in the absence of structural markers, partially automating the process of interpretation of semantic nonce words. Presence of word-building elements in the structure of ІехісаІ nonce word, appearing on the principle of analogy, and containing evaluation, gives an element of predictability to the process of interpretation.